Adsorption of Mono Substituted Nitro Phenols From Aqueous Solution on the Zemeej Surface at Different Temperatures - AL-Abodi, Entisar E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Adsorption of o-Nitrophenol (o-Nph), m- Nitrophenol (m-Nph) and p- Nitrophenol (pNph) on the sedimentary sand of the Tigress River which is known locally by â€œZemeejâ€ from aqueous solution at 288, 298, 308, 318 and 328 k0 . This study indicates that o-Nph and mNph take multi-layered S type according to Giles classification while p-Nph takes a multilayered L type according to the same classification. The isotherms treated by Freundlich model and show a good response to this model because the heterogeneous nature of the surface. The adsorption for all materials was endothermic as shown from Î”H values and explained through the porous nature of the surface, the remaining thermodynamic functions Î”G and Î”S were also calculated at all temperatures for all adsorbents which indicate that the randomness, finally the results indicate that the orientation on NO2 group to para position acts to decrease the quantity of adsorption